Heavy metals immobilization and improvement in maize (Zea mays L.) growth amended with biochar and compost - Irfan, Muhammad; Mudassir, Muhammad; Khan, Muhammad Jamal; Dawar, Khadim Muhammad; Muhammad, Dost; Mian, Ishaq Ahmad; Ali, Waqas; Fahad, Shah; Saud, Shah; Hayat, Zafar; Nawaz, Taufiq; Khan, Shah Alam; et al. (Scientific reports, 2021)
Soil with heavy metals contamination, mainly lead (Pb), cadmium (Cd), and chromium (Cr) is a progressively worldwide alarming environmental problem. Recently, biochar has been used as a soil amendment to remediate contaminated soils, but little work has been done to compare with other organic amendments like compost. We investigated biochar and compost's comparative effect on Pb, Cd, and Cr immobilization in soil, photosynthesis, and growth of maize plants. Ten kg soil was placed in pots and were spiked with Pb, Cd, and Cr at concentrations 20, 10, 20 mg kg-1. The biochar and compost treatments included 0, 0.5, 1, 2, and 4% were separately applied to the soil. The crop from pots was harvested after 60 days. The results show that the highest reduction of AB-DTPA extractable Pb, Cd, and Cr in soil was 79%, 61% and 78% with 4% biochar, followed by 61%, 43% and 60% with 4% compost compared to the control, respectively. Similarly, the highest reduction in shoot Pb, Cd, and Cr concentration was 71%, 63% and 78%with 4% biochar, followed by 50%, 50% and 71% with 4% compost than the control, respectively. The maximum increase in shoot and dry root weight, total chlorophyll contents, and gas exchange characteristics were recorded with 4% biochar, followed by 4% compost than the control. The maximum increase in soil organic matter and total nitrogen (N) was recorded at 4% biochar application while available phosphorus and potassium in the soil at 4% compost application. It is concluded that both biochar and compost decreased heavy metals availability in the soil, reducing toxicity in the plant. However, biochar was most effective in reducing heavy metals content in soil and plant compared to compost. In the future, more low-cost, eco-friendly soil remediation methods should be developed for better soil health and plant productivity.